Mindfulness and trial-based cognitive therapy for the psychological well-being in the judiciary: A controlled and randomized study protocol - Sara Bitencourt; Bo-Huei Huang; Irismar Reis de Oliveira; Marcelo Demarzo (MethodsX)
Introduction: The judiciary sector faces high absenteeism due to mental health issues, yet applying effective therapies like mindfulness and trial-based cognitive therapy (TBCT) remains unexplored. Objectives: Develop and apply Mindfulness-Integrated Trial-Based Cognitive Therapy (M-TBCT) in the judiciary to assess its acceptability, feasibility, and efficacy in enhancing psychological well-being and reducing depression, anxiety, and improving self-care. Methods: Conduct a controlled, randomized study in two phases: Phase 1 involves a pilot study to structure the M-TBCT protocol and test its acceptability and feasibility in the judiciary (N = 30); Phase 2, an efficacy trial with 90 participants, comparing M-TBCT to a waitlist. M-TBCT consists of 8 online, individual, weekly sessions. Participants recruited via SRQ-20, with WHO-5, PHQ-9, GAD-7, CD-QUEST and ASAS-R as outcomes. Expected outcomes: M-TBCT is expected to be acceptable, feasible, and effective in improving psychological well-being, reducing anxiety, depression, and enhancing self-care, with sustained benefits at a 6-month follow-up. Conclusions: This study introduces a novel psychotherapeutic approach to address mental well-being and self-care in the judiciary.